Occurrence of the alien kelp Undaria pinnatifida (Laminariales, Phaeophyceae) in Mar del Plata, Argentina - Meretta, Pablo Ezequiel (2012)
Undaria pinnatifida (Harvey) Suringar 1873 is native to Northern Asia and has become well established in the Mediterranean Sea, Atlantic Europe, New Zealand, Tasmania, Australia, Pacific coasts of United States and Mexico and Patagonia Argentina. On the 13th of September of 2011 sporophytes of U. pinnatifida were found growing from the subtidal-intertidal limit to 4.5 m depth in Mar del Plata. This contribution brings the first Undaria pinnatifida report in Mar del Plata and extends 1300 km the northern distribution limit of this kelp in Argentina.